(untitled) (Politeja, 2014)
Green Folks of Padania. Tribal Fantasies and Economic Interests of the Italian Separatists The article presents the genesis and the evolution of the Northern Italian separatist movement initially aiming at the foundation of the autonomist Padanian Republic. Among the main dimensions of the pro‑independence tendencies manifested by the members and followers of the Northern League party there are ethno‑linguistic diverseness and strong economic position which distinguishes the Northern regions of Italy from the rest of its territory. The article focuses on the analysis of both socio‑cultural and political‑economic backgrounds of the separatist tendencies. It underlines the special role of Celtic mythology and pagan symbols in the construction of the Padanian identity. The strategies of the political communication of the Northern League are described in relation to the Padanian rhetoric manifested through the electoral posters and slogans of the party.